Validation of an asthma questionnaire for use in healthcare workers. Issue 3 (23rd February 2006) - Delclos, G L; Arif, A A; Aday, L; Carson, A; Lai, D; Lusk, C; Stock, T; Symanski, E; Whitehead, L W; Benavides, F G; Antó, J M
Abstract : Background: Previous studies have described increased occurrence of asthma among healthcare workers, but to our knowledge there are no validated survey questionnaires with which to study this occupational group. Aims: To develop, validate, and refine a new survey instrument on asthma for use in epidemiological studies of healthcare workers. Methods: An initial draft questionnaire, designed by a multidisciplinary team, used previously validated questions where possible; the occupational exposure section was developed by updating health services specific chemical lists through hospital walk-through surveys and review of material safety data sheets. A cross-sectional validation study was conducted in 118 non-smoking subjects, who also underwent bronchial challenge testing, an interview with an industrial hygienist, and measurement of specific IgE antibodies to common aeroallergens. Results: The final version consisted of 43 main questions in four sections. Time to completion of the questionnaire ranged from 13 to 25 minutes. Test–retest reliability of asthma and allergy items ranged from 75% to 94%, and internal consistency for these items was excellent (Cronbach's α ⩾ 0.86). Against methacholine challenge, an eight item combination of asthma related symptoms had a sensitivity of 71% and specificity of 70%; against a physician diagnosis of asthma, this same combination showed a sensitivity of 79% and specificity of 98%. Agreement between self-reported exposures and industrial hygienist review was similar to previous studies and only moderate, indicating the need to incorporate more reliable methods of exposure assessment. Against the aerollergen panel, the best combinations of sensitivity and specificity were obtained for a history of allergies to dust, dust mite, and animals. Conclusions: Initial evaluation of this new questionnaire indicates good validity and reliability, and further field testing and cross-validation in a larger healthcare worker population is in progress. The need for development of more reliable occupational exposure assessment methods that go beyond self-report is underscored.